Diabetes is associated with a higher incidence of short-term mortality risk and readmission in patients who undergo surgical but not transcatheter aortic valve replacement - Soha Dargham; Amin Jayyousi; Jassim Al Suwaidi; Charbel Abi Khalil; Ahston D Souza; Khalifa Bsheish (Open Heart)
Background Transcatheter aortic valve replacement (TAVR) is increasingly used for aortic valve replacement instead of surgical aortic valve replacement (sAVR). We aimed to examine the impact of diabetes on 30-day mortality, 30-day readmission and compare outcomes between TAVR and sAVR.Methods Data were extracted from the Nationwide Readmissions Database from 2012 to 2017. The primary outcome was 30-day mortality, and the secondary outcome was 30-day readmission.Results The study included 110 135 patients who underwent aortic valve replacement. Of these, 59 466 (54.0%) were hospitalised for TAVR, and 50 669 (46.0%) underwent sAVR. Diabetes was present in 36.4% of TAVR patients and 29.1% of sAVR patients. In TAVR patients, the adjusted risk of 30-day readmission and mortality was similar regardless of diabetes status (aHR=0.94 (0.86–1.03); 0.97 (0.84–1.12); respectively). However, sAVR patients with diabetes had a higher adjusted risk of 30-day mortality (aHR=1.13 (1.01–1.25)) but not readmission (aHR=0.92 (0.84–1.01)). When comparing outcomes between TAVR and sAVR in patients with diabetes, TAVR patients were older and had a higher prevalence of chronic kidney disease (CKD). Nevertheless, 30-day readmission and mortality were lower in patients who underwent TAVR (aHR=0.59 (0.53–0.67), aHR=0.29 (0.25–0.34), respectively) compared with sAVR. Coronary artery disease was the most significant predictor of readmission in patients with diabetes. CKD increased the risk of mortality by almost twofold in both techniques.Conclusion Diabetes increases the risk of short-term mortality in sAVR but not TAVR. Moreover, the incidence of 30-day mortality and readmission is lower in TAVR compared with TAVR among patients with diabetes.